TINJAUAN UNDANG-UNDANG DAN FATWA MUI TERKAIT EFEKTIVITAS PENGELOLAAN DANA ZAKAT - Wijaya, Rusdiana Priatna; Suwandi, Asril (INSTITUT AGAMA ISLAM TAZKIA, 2021)
The purpose of this research was to examine the effectiveness of the distribution of zakat funds at Baitul Maal Tazkia. The method used is Mixed Method (qualitative and quantitative), qualitative method in this case the author obtains primary data from field observations, direct documentation, interviews with the Chairman or Staff of Baitul Maal Tazkia and literature studies. While the quantitative method using the 10th Zakat Core Principle measurement ratio is DCR (Disbursement Collection Ratio) Based on ZCP, the effectiveness of Baitul Maal Tazkia's distribution of zakat funds for 4 years of operation is 55% or is included in the Fairly Effective category (quite effective) where the Disbursement Collection Ratio (DCR) reaches 50-69 percent, with the amount collected during the 2017 to 2017 period. 2020 amounting to Rp 4,536,153,278. While the amount of distribution during the period 2017 to 2020 is IDR 2,472,687,990.